Implementing complex rehabilitation interventions in research: the example of vocational rehabilitation for people with traumatic brain injury - Holmes, Jane A. (2018)
Background: Research does not always translate into improved patient outcomes because of difficulties implementing complex health interventions. Distinguishing between effectiveness and factors affecting implementation is critical to improving trials of rehabilitation interventions. Understanding barriers and facilitators encountered when delivering complex interventions, such as rehabilitation, in the research environment requires examination. Implementation research is the study of methods to promote the uptake of research findings into routine practice and can help identify and explain barriers and facilitators. The aim of this project was to understand factors that affect the delivery of complex rehabilitation interventions in research, focussing on vocational rehabilitation for people with traumatic brain injury.